Tetra-n-butylammonium fluoride-mediated dimerization of (α-methylbenzylidene)malononitriles to form polyfunctional 5,6-dihydropyridines derivatives under solvent-free conditions - Hameed, Abdul; Anwar, Ayaz; Yousaf, Sammer; Khan, Khalid Mohammed; Basha, Fatima Zahra (European Journal of Chemistry, 2012)
A series of polyfunctional dihydropyridine 28-46 were prepared via dimerization of readily available substituted (a-methylbenzylidene)-malononitriles 10-27 by treating with neat TBAF.3H2O under solvent-free conditions at 85-90 oC. All the dimers 28-46 were obtained in high yield from their corresponding substituted alkylidenemalononitriles except in the case of 2-chloro (15), 2-hydroxy (21), and 2-nitro (26) substituted alkylidenemalononitriles where the reaction was unsuccessful due to the steric interaction between methylene group and the substituents present at ortho position. The X-ray crystallographic studies of compounds 28 and 30 were carried out to confirm the structure of dimerized product. The method is eco-friendly and wider is scope to prepare a range of substituted dihydropyridine derivatives 28-46.